Adrenal failure due to bilateral adrenal metastasis of rectal cancer: A case report - Imaoka, Yuki (Int J Surg Case Rep, 2016)
INTRODUCTION: It is rare for a patient to present with adrenal insufficiency secondary to bilateral adrenal metastases from a malignant colorectal tumor. CASE PRESENTATION: An 82-year-old Japanese man presented to our hospital with high fever and malaise. He was receiving oral chemotherapy for the treatment of rectal cancer with multiple metastases. Computed tomography showed new bilateral adrenal gland metastases. A rapid adrenocorticotropic hormone (ACTH) test showed adrenal insufficiency. Treatment with hydrocortisone provided immediate symptom improvement. DISCUSSION: Adrenal insufficiency secondary to bilateral adrenal metastases from rectal cancer is rare. A rapid ACTH test is useful to diagnose adrenal insufficiency. CONCLUSION: The incidence of adrenal insufficiency may be underestimated in patients with multiple metastasis. Appropriate therapy with adrenal corticosteroid hormone supplementation may lead to a significant improvement in the patient’s symptoms and quality of life.